Energy Drink Consumption Practices of Young People in Bahrain - Maryam M. Nassaif; Ghufran J. J. Alobed; Noor A. A. Alaam; Abdulla N. Alderrazi; Muyssar S. Awdhalla; Asokan G. Vaithinathan (University Library System, University of Pittsburgh, 2016)
Background: Energy drink (ED) consumption is becoming increasingly popular among young Bahrainis, who may be unaware of the health risks associated with ED consumption. To date, there have been few publications on the consumption of ED in Bahrain, particularly among adolescents. This study seeks to fill a gap in the literature on energy drink consumption practices of Bahraini adolescents. Methods: Data were collected using a previously established European Food Safety Authority questionnaire. Cross-sectional analyses were conducted on a convenience sample of 262 Bahraini students aged 10 to 18 years. Results: Most participants consumed energy drinks 2 to 3 times per week and consumed two or more cans at a time. Eighty percent of partcipants preferred energy drinks with sugar. Participants in the older age group and higher educational level consumed more ED. The majority (57%) consumed ED at home with friends as part of socialization. Notably, 60% of the parents of the respondents have not consumed energy drinks. Prominent reasons for consumption of energy drinks included: taste (40%), energy (30%), stay awake (13%), augment concentration (4%), and enhance sports performance (6%). Conclusion: Energy drink consumption is a popular socialization activity among adolescents of Bahrain. The potential health risks necessitates the need for novel health promotion strategies and advocacy efforts for healthy hydration practices.